Use of Information and Communication Technology for Quality Management in the Classroom - Pauta-Ruales, Paulina (2024)
The purpose of this study was to analyze the use of Information and Communication Technologies (ICT) for quality classroom management at the Doctor Eduardo Mora Moreno High School in Loja, Ecuador. It was developed in the positivist paradigm, with quantitative approach, in a field research type with descriptive level, non-experimental transectional design with a population and census sample of fifteen (15) tenured teachers in classroom functions. To collect the information, an instrument containing twenty-four (24) items with response alternatives on an estimation scale (always, almost always, sometimes, almost never and never) was designed; it was subjected to content validity using the expert judgment technique and reliability with Cronbach's Alpha internal consistency method, where the result obtained was 0.92, indicating that the instrument presented strong reliability. For data analysis, descriptive statistics were used to obtain information from classroom teachers regarding the use of various ICT tools. In spite of the permanent training offered by the governing body, it was concluded that the classroom management of the professionals does not attend to the stages of planning, organization, leadership and evaluation with the use of ICT, which limits the achievement of educational quality in terms of equity, effectiveness and efficiency.